Business Strategy for Company XYZ Dealing with Domestic Content Requirement in Indonesia Oil and Gas Industry - Syamra, Arif Budiman; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2013)
The 2nd revision of PTK (Peraturan Tata Kerja) No. 007 by BP Migas (Indonesia Oil and Gas Regulatory Body, now called SKP Migas) contains a very strong Nationalization spirit to encourage domestic products and services leveraged. This revision, as stipulated in tender bid documents, requires a comprehensive local content achievement by Contractors, where bidders must meet at least minimum 35% of total products and services offered in their bid proposal are coming from domestic products and services. To some extent of tender scopes, only 2 or 3 international companies only that technically qualified for the works, however these international companies couldnâ€™t achieved this 35% domestic content requirement, while in the other hand, all existing national companies and have better percentage of domestic content utilization, are technically incompetence to perform the requested works.Â